Computed eigenmodes of planar regions - Trefethen, L; Betcke, T (Unspecified, 2005)
Recently developed numerical methods make possible the high-accuracy computation of eigenmodes of the Laplacian for a variety of "drums" in two dimensions. A number of computed examples are presented together with a discussion of their implications concerning bound and continuum states, isospectrality, symmetry and degeneracy, eigenvalue avoidance, resonance, localization, eigenvalue optimization, perturbation of eigenvalues and eigenvectors, and other matters. Timo Betcke was supported by a Scatcherd European Scholarship.